2000
DOI: 10.1501/intrel_0000000019
|View full text |Cite
|
Sign up to set email alerts
|

United Nations' Changing Role in the Post-Cold War Era

Abstract: This article analyzes the changing role of the United Nations in the post-Cold War era. After the end of the Cold War, many internal conflicts broke out in different parts of the world. There was a dramatic demand for the UN peacekeeping operations. Thus, the UN started to challenge traditional norms of international politics, such as state sovereignty, non-intervention into domestic affairs, and non-use of force in peacekeeping operations, and itself as an international organization. Within this context, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Further the Korean War was the most significant example, which showed that the UN became an arena of ideological struggle between the two poles. During the Korean War, the UN moved from being simply a forum for diplomatic pressure and propaganda to play a forceful role in a way not envisaged by the Charter (Latif, 2000).…”
Section: Ijoess June 2019 573mentioning
confidence: 99%
“…Further the Korean War was the most significant example, which showed that the UN became an arena of ideological struggle between the two poles. During the Korean War, the UN moved from being simply a forum for diplomatic pressure and propaganda to play a forceful role in a way not envisaged by the Charter (Latif, 2000).…”
Section: Ijoess June 2019 573mentioning
confidence: 99%
“…The Korean War, Suez Canal Crisis and the UN operation in Congo were the most important examples, which showed that the UN became an arena of ideological struggle between the two blocs [Latif 2000].…”
Section: Cold War Periodmentioning
confidence: 99%
“…Soğuk savaş döneminin sona ermesiyle birlikte; iki kutuplu dünya düzeninden, Birleşmiş Milletler'in daha etkin olacağı bir yapıya geçilmesi beklenmiştir (Latif, 1999). Küreselleşmenin yaygınlaşması, dünya ekonomisinde yaşanan hızlı büyüme ve bu büyümenin etkilediği varsayılan kurumsal yapılarla birlikte; ulus devletlerin birbirleriyle olan ilişkileri küresel düzeyde artış göstermektedir.…”
Section: Introductionunclassified